1977
DOI: 10.1039/f29777300135
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spectrum of the manganate(V) ion

Abstract: The polarized electronic spectrum of MnO2-doped in crystals of Ca2PO4C1 has been measured at 4.2 K from 5000 to 40 000 cm-'. From a careful examination of the possible excited states and of the lattice site-group perturbation, the four observed bands in the region 8000-24000cm-' are assigned as ligand field bands and the other two more intense beyond 24 000 cm-' are assigned as charge transfer. The assignments are supported by the observed polarizations and by ligand field calculations which give a good fit to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The band splitting and the polarization properties of the investigated compound can then be discussed in the frame of the D 2d symmetry group, in agreement with previous literature [8,9]. The consistency between experimental and calculated transition energies is satisfactory, and the considerations presented above about the transitions to the singlet states are valid also in this case.…”
Section: Mno 4 3à In Ca 2 Po 4 CLsupporting
confidence: 77%
See 3 more Smart Citations
“…The band splitting and the polarization properties of the investigated compound can then be discussed in the frame of the D 2d symmetry group, in agreement with previous literature [8,9]. The consistency between experimental and calculated transition energies is satisfactory, and the considerations presented above about the transitions to the singlet states are valid also in this case.…”
Section: Mno 4 3à In Ca 2 Po 4 CLsupporting
confidence: 77%
“…In particular, in the Li 3 PO 4 and Sr 5 (PO 4 ) 3 Cl spectra the expected position of the 3 T 1 ( 3 P) level does not correspond to intense and well recognizable absorption features. In this connection we firstly point out that the mean energies of the triplet states have been reproduced only on the basis of the B Racah parameter, whose values, consistent with literature data [8,9] allow the correct positioning of the low energy manifolds. In addition, it can be observed that the absorption behaviour in the high energy side of these spectra is complicated by the concurring of singlet, triplet and charge transfer transitions having different allowances and interacting between them through several quite different mechanisms, like Table 3 Calculated energy levels (in cm À1 ) for Mn 5+ ion in all considered crystals (only the lowest energy levels lying in the spectral measurements region are reported).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…11,12 Although the manganate(V) ion has been the subject of several studies involving molecular orbital calculations, 13 -17 and electronic, 18 -24 fluorescence, 18,25 -27 ESR, 19,24,27 -29 infrared 30 -33 and Raman 32 -34 spectroscopy, there is no report on resonance Raman investigations that could help in the assignment of its electronic transitions and electronic structure, a point that remains controversial in the literature. Some workers, supported by theoretical calculations and comparison with correlated systems, claim that below 30000 cm 1 there are no charge-transfer (CT) transitions, 20,21 whereas others sustain that this is not true. 17 -19 The ground-state configuration for the manganate(V) ion is 1a 1 2 1t 2 6 1e 4 2t 2 6 1t 1 6 2e 2 3t 2 0 .…”
Section: Introductionmentioning
confidence: 99%